Nurses' competencies in health promotion for homebound older people - Telma Alteniza Leandro; Allana Mirella Alves; Ana Karina Bezerra Pinheiro; Thelma Leite de Araujo; Glauberto da Silva Quirino; Dayanne Rakelly de Oliveira (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to identify competencies related to health promotion targeting homebound older people, as they appear in the literature. Method: systematic review using the LILACS, Scopus, CINAHL, PubMed and Cochrane Library databases. The search was performed in November 2017. Selected articles were analyzed according to nine competency domains: enable change; advocate for health; mediate through partnership; communication; leadership; assessment; planning; implementation, and evaluation and research. Results: nine clinical trials were included. All health promotion competency domains were identified in the reviewed research interventions, performed with homebound older people. Conclusion: studies showed that the employed treatments were beneficial for the homebound older population. Interventions based on health promotion competencies were positively identified, and are linked to an effective and high-quality health care practice.